Key Success Factors of the Hua Hin Agricultural Cooperative Limited - Orsuwan, Nasorn; Suebpongsakorn, Auttapol (Princess of Naradhiwas University Journal of Humanities and Social Sciences, 2022)
The objectives of this research were 1) to study factors affecting to Hua Hin Agricultural Cooperative Limited’s operating success in management, 2) to study the success of Hua Hin Agricultural Cooperative Limited and 3) to examine the effects of factors affecting to Hua Hin Agricultural Cooperative Limited’s operating success in management. The samples were 251 cooperative members and non-members. The instrument used to collect data was a questionnaire which received its validity at 1.0 and reliability over 0.70. Data were analyzed by descriptive statistics; frequency, percentage, mean and standard deviation, inferential statistics; F-test, One-way ANOVA, ordered probit regression and marginal effect. The results from means and ordered probit regression analysis showed that the governance structure factor affects the operating success in management of Hua Hin Agricultural Cooperative Limited. The Hua Hin Agricultural Cooperative Limited’s operating success in management was measured by objectives achievement, members’ trust and members’ happiness.